The relational geographies of the voluntary sector: Disentangling the ballast of strangers. (October 2020) - DeVerteuil, Geoffrey; Power, Andrew; Trudeau, Dan
We propose that voluntary sector geographies are best understood using a systematic relational approach, drawing upon neo-Marxist and symbiotic perspectives. We focus on relations between the voluntary sector and the (shadow) state, internal spaces of client interaction, and external urban spaces. Our relational approach advances alternative understandings of the voluntary sector: ones that are partly but not fully in the orbit of the shadow state; more mediator than conduit for neoliberal policies; partly punitive, yet firmly in relation with other ambivalent measures for clients; and both spatially uneven and fixed, but always unbounded in its practices.